Digital Activism in the Petition "Return Donor Money": A Phenomenological Study of Muslim Activists in Bogor, Indonesia - Elis Teti Rusmiati; Yunita Sari; Derysmono Derysmono; Sunarto Sunarto; Edin M. Utoh Talum (JURNAL INDO-ISLAMIKA, 2026)
This study explores the lived experiences and meanings constructed by Muslim activists in Bogor Regency in relation to digital activism through the online petition “Return Donor Money.” The study addresses the limited attention given to the subjective, emotional, and faith-based dimensions of local Muslim participation in digital activism, particularly when online mobilization is connected to issues of transparency, accountability, and Islamic social solidarity. Using a qualitative phenomenological approach, this research draws on semi-structured in-depth interviews with five participants, consisting of mosque activists, a humanitarian volunteer, a blogger, an NGO activist, and a local religious leader. The data were analyzed through Moustakas’ phenomenological procedures, including epoche, horizonalization, clustering of meanings, and thematic interpretation, supported by observation and social media monitoring. The findings show that the petition functioned not only as a digital instrument for demanding financial accountability but also as a moral space for expressing concern, strengthening collective identity, and mobilizing solidarity among Muslim communities. Participants interpreted their involvement as non-violent resistance, ethical advocacy, and an effort to protect the value of taʿāwun within Islamic philanthropy. However, the study also reveals tensions related to misinformation, public skepticism, echo chambers, digital inequality, and digital dualism between online and offline identities. The study contributes to digital activism and Islamic communication scholarship by demonstrating that online petitions may operate as telepresence, enabling Muslim activists to transform moral awareness into collective advocacy and social change.